At-a-glance - An update on positive mental health among adults in Canada - Varin, Mlanie (Health Promot Chronic Dis Prev Can, 2020)
This At-a-glance presents updated estimates for the Positive Mental Health Surveillance Indicator Framework for adults aged 18 years and older. Using data from the 2015 and 2017 Canadian Community Health Survey, we calculated the prevalence of positive mental health and associated determinants. Estimates for positive mental health outcomes for adults ranged from 68.1% to 87.1%. We also explored the associations between sociodemographic factors and positive mental health among adults in Canada. Our findings suggest sociodemographic differences in odds of self-rated mental health, happiness, life satisfaction, and psychological and social well-being.